Swift, Joyce, and the Flight from Home Quests of Transcendence and the Sin of Separation - Atkins, G.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Pivot, 2014)
In a fresh reading of Gulliver's Travels and A Portrait of the Artist as a Young Man, Atkins draws parallels between the protagonists: both Lemuel Gulliver and Stephen Dedalus flee from the burdens of life, seeking a transcendent existence. The study sheds important new light on both novels as essential critiques of modern misunderstandings.
Keywords: Literature, Modern—20th century; British literature; Literature—Philosophy.; Fiction; Literature—History and criticism; Poetry; Twentieth-Century Literature; British and Irish Literature; Literary Theory; Fiction; Literary History; Poetry and Poetics